The ventricular late potentials in children with vasodepressor response of vasovagal syncope. (1st October 2016) - Zou, Runmei; Li, Yunli; Wu, Lijia; Li, Wen; Li, Fang; Lin, Ping; Xie, Zhenwu; Wang, Cheng
Abstract: Objectives: To discuss ventricular late potentials (VLPs) in children with vasodepressor response of vasovagal syncope (VVS-V). Methods: 184 children diagnosed as VVS-V by head-up tilt test (HUTT) were enrolled as VVS-V group, 105 age and gender matched healthy individuals without syncope were used as control group, then signal-averaged electrocardiogram was measured. Results: HR was decreased [(83.98 ± 12.27) vs (87.28 ± 13.75) bpm, P  < 0.05] in VVS-V group compared with control group. The prevalence of positive VLPs was not significantly different between the two groups. However the absolute values of TQRS [(84.89 ± 12.05) vs (81.21 ± 8.23) ms, P  < 0.01], RMS40 [(28.73 ± 7.23) vs (26.89 ± 7.36) μV, P  < 0.05] and LAS40 [(62.43 ± 19.17) vs (56.79 ± 1.83) ms, P  < 0.05] were significantly prolonged in VVS-V group compared with control group, and more patients in VVS-V group had abnormal prolonged LAS40 (94.57% vs 83.80%, P  < 0.01). Conclusions: The prevalence of positive VLPs was not significantly different, TQRS, RMS40, LAS40 were longer in children with VVS-V in comparison with healthy individuals, and the abnormal LAS40 occurred in a higher proportion of VVS-V group.